Four PTEN‐targeting co‐expressed miRNAs and ACTN4‐ targeting miR‐548b are independent prognostic biomarkers in human squamous cell carcinoma of the oral tongue. Issue 11 (18th August 2017) - Berania, Ilyes; Cardin, Guillaume B.; Clément, Isabelle; Guertin, Louis; Ayad, Tareck; Bissada, Eric; Nguyen‐Tan, Phuc Felix; Filion, Edith; Guilmette, Julie; Gologan, Olguta; Soulieres, Denis; Rodier, Francis; et al.
Abstract : The purpose of this study was to determine the prognostic value and oncogenic pathways associated to miRNA expression in squamous cell carcinoma of the oral tongue and to link these miRNA candidates with potential gene targets. We performed a miRNA screening within our institutional cohort ( n = 58 patients) and reported five prognostic targets including a cluster of four co‐expressed miRNAs (miR‐18a, miR‐92a, miR‐103, and miR‐205). Multivariate analysis showed that expression of miR‐548b ( p = 0.007) and miR‐18a ( p = 0.004, representative of co‐expressed miRNAs) are independent prognostic markers for squamous cell carcinoma of the oral tongue. These findings were validated in The Cancer Genome Atlas (TCGA) cohort ( n = 131) for both miRNAs (miR‐548b: p = 0.027; miR‐18a: p = 0.001). Bioinformatics analysis identified PTEN and ACTN4 as direct targets of the four co‐expressed miRNAs and miR‐548b, respectively. Correlations between the five identified miRNAs and their respective targeted genes were validated in the two merged cohorts and were concordantly significant (miR‐18a/PTEN: p < 0.0001; miR‐92a/PTEN: p = 0.0008; miR‐103/PTEN: p = 0.008; miR‐203/PTEN: p = 0.019; miR‐548b/ACTN4: p = 0.009). Abstract : What's new? MicroRNAs (miRNAs) are increasingly recognized as key regulatory factors in cancer. This study examined their significance specifically in the context of squamous cell carcinoma of the oral tongue (SCCOT). Co‐expression of four miRNAs was found to be inversely correlated with expression of the tumor suppressor PTEN, a downregulator of PI3K/Akt signaling, which is frequently altered in cancer. Increased expression of an additional miRNA, miR‐548b, was inversely correlated with ACTN4, an Akt regulator. The miRNAs were further associated with SCCOT patient prognosis. The findings highlight potential prognostic and therapeutic avenues centering on miRNAs in oral tongue carcinoma.